Analysis of Muscle Fatigue During Prolonged Standing Jobs in Manufacturing Industry Utilizing Ergonomics Assessment - Isa, Halim (2010)
Many jobs in manufacturing industry require workers to spend most of their working hours in prolonged standing. The working position may lead to muscle fatigue. Muscle fatigue can be defined as decline of maximum strength of worker, changes of electromyography (EMG) signals, and increases in subjective rating of discomfort. The objectives of this study are to determine subjective fatigue experienced by production workers who are exposed to prolonged standing jobs, and assess muscle fatigue in their lower extremities. The subjective fatigue was obtained through questionnaire surveys. Meanwhile, muscle fatigue has been analyzed using surface electromyography (sEMG). Six muscles: left and right erector spinae muscles, left and right tibialis anterior muscles, and left and right gastrocnemius muscles were concurrently measured more than five hours of standing to obtain muscle fatigue in the lower extremities of workers. Ten production workers in a metal stamping company participated as subjects in this study. The subjects were required to undergo both questionnaire survey and muscle fatigue assessment. Results of questionnaire surveys found that all subjects reported that they experienced muscle fatigue due to prolonged standing jobs. Similarly, muscle fatigue has been identified through sEMG measurement. Based on this study, the authors found that there is a positive correlation between both assessments; hence prolonged standing jobs can be hypothesized as a contributor to muscle fatigue among industrial workers in manufacturing industry.